Stacked Digital Imaging of Foraminifera - Peter Lunt (Berita Sedimentologi, 2014)
This paper describes a technique of imaging foraminifera by combining a series of digital photographs in automated software to produce a single optical image with high resolution and superior depth of focus. Results can be obtained that are nearly as good as low-power SEM images, but have the great advantage of showing the hyaline tests as they appear to the working eye under a binocular microscope, as the foraminifera do not need to be coated in gold.Digital imaging should be utilised more in documentation of foraminifera. The benefits of a low-cost and easy method of imaging include faster learning of new faunas, leading to more consistent species concepts. Workers can now publish fully illustrated works on complex morphometric series. Commercial service companies can now illustrate important taxa / faunal components and emphasise good micropalaeontological data in a way that the written word cannot.